(untitled) (Confluenţe Bibliologice, 2023)
This article is about the artistic-didactic seminar "Music, poetry, human voice - multitude of poses", dedicated to the young poet and performer Laura Mogorean, a student at the , George Enescu" National University of Arts in Iași.